Factors determining the quality and efficiency of the two-level local government model - NGUYỄN BÁ CHIẾN (Political Theory Journal, 2026)
The article analyzes the determining factors of quality and efficiency after one year of operating the two-level local government model. Based on modern public governance theory and operational practices, the article observes that the model's efficiency depends not only on streamlining the organizational apparatus, but primarily on institutional quality, the extent of substantive decentralization, the governance capacity of governments at all levels, the quality of public human resources, the development level of digital government, resource allocation mechanisms, power control, and governance culture. Thereby, the article proposes orientations to enhance the quality and efficiency of the model toward a modern, people-centered approach.
Keywords: two-level local government; power control; decentralization; governance capacity; digital government.